THE INFLUENCE OF THE ROLE OF INTERNAL AUDIT, AUDIT COMMITTEE CHARACTERISTICS AND INTERNAL CONTROL ON FRAUD PREVENTION - Kurniasih, Tuspeni; Sari, Intan Rahma (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2024)
This research aims to determine the influence of the role of internal audit, characteristics of the audit committee and internal control on fraud prevention at the Jakarta People's Credit Bank. The population in this study was 35 People's Credit Banks (BPR). Based on the Slovin formula method, the total research sample obtained was 26 respondents. This research is a type of quantitative research with the data collection method used is primary data, namely data in the form of opinions from research subjects (respondents) using a survey method obtained through filling out questionnaires by respondents. The data in this research was obtained from distributing questionnaires. Hypothesis testing in this research uses the multiple linear regression analysis method which is processed using SPSS 25. Based on the test results, it was found that the role of internal audit, characteristics of the audit committee and internal control simultaneously have a significant effect on fraud prevention. This research also found that the role of internal audit has no effect on fraud prevention. Meanwhile, the characteristics of the audit committee and internal control influence fraud prevention.